2023
DOI: 10.1017/s0144686x22001350
|View full text |Cite
|
Sign up to set email alerts
|

Living with dementia during the COVID-19 pandemic: insights into identity from the IDEAL cohort

Abstract: The continuing COVID-19 pandemic and social restrictions have impacted on the cognitive decline and mental health of people with dementia. Social isolation and loss of activities due to social restrictions may also have implications as to sense of identity for people with dementia. As part of the INCLUDE (Identifying and Mitigating the Individual and Dyadic Impact of COVID-19 and Life Under Physical Distancing on People with Dementia and Carers) component of the IDEAL (Improving the Experience of Dementia and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 73 publications
1
4
0
Order By: Relevance
“…Our findings uphold early concerns about the impact social isolation may have on psychosocial wellbeing ( Clare et al, 2022 ; Pentecost et al, 2022 ; Rising et al, 2022 ), highlighting the distress caused by awareness of negative changes attributed to reduced social activity and doubts about whether such skills can be restored. Encouragingly, this study, similar to earlier research ( O'Rourke et al, 2021 ; Pentecost et al, 2022 ; Stapley et al, 2022 ), found people with dementia continued to exhibit signs of resilience, responding to new challenges by identifying new and existing strategies to support everyday life with dementia.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Our findings uphold early concerns about the impact social isolation may have on psychosocial wellbeing ( Clare et al, 2022 ; Pentecost et al, 2022 ; Rising et al, 2022 ), highlighting the distress caused by awareness of negative changes attributed to reduced social activity and doubts about whether such skills can be restored. Encouragingly, this study, similar to earlier research ( O'Rourke et al, 2021 ; Pentecost et al, 2022 ; Stapley et al, 2022 ), found people with dementia continued to exhibit signs of resilience, responding to new challenges by identifying new and existing strategies to support everyday life with dementia.…”
Section: Discussionsupporting
confidence: 82%
“…Nevertheless, it is not without limitations. In order to achieve our comparison, recruitment was limited to a pool of participants who had previously taken part in IDEAL-CDI or INCLUDE interviews ( O'Rourke et al, 2021 ; Pentecost et al., 2022 ; Stapley et al, 2022 ) and were able to be interviewed at this time point. The sociodemographic profile of our sample was limited to white British individuals mostly living with young-onset dementia, and four of the nine participants were University educated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations